(untitled) (Medico Legal Update, 2021)
Urolithiasis is a common disease worldwide and affects a wide gamut of the patient population, irrespective of race, culture or geographic boundaries. In the past few decades, there has been an increasing incidence of urinary stone disease both in developed and developing nations due to changes in life style, particularly due to the rising prevalence of obesity. MDCT plays a critical role in the management of patients with urolithiasis. Their applicability ranges from the initial diagnosis to planning treatment strategies and in post-treatment follow-up. The emerging technological innovations in CT are bridging the gap between radiological interpretations and urologists’ expectations. With the widespread implementation of low-dose protocols and iterative reconstruction algorithms in routine clinical practice, the radiation dose concerns can be minimized without affecting the diagnostic yield of the CT exams